Postmastectomy Radiation Therapy (PMRT) before and after 2-Stage Expander-Implant Breast Reconstruction: A Systematic Review - Jeremie D. Oliver; Daniel Boczar; Maria T. Huayllani; David J. Restrepo; Andrea Sisti; Oscar J. Manrique; Peter Niclas Broer; Sarah McLaughlin; Brian D. Rinker; Antonio Jorge Forte (Medicina, 2019)
Background: In those undergoing treatment for breast cancer, evidence has demonstrated a significant improvement in survival, and a reduction in the risk of local recurrence in patients who undergo postmastectomy radiation therapy (PMRT). There is uncertainty about the optimal timing of PMRT, whether it should be before or after tissue expander or permanent implant placement. This study aimed to summarize the data reported in the literature on the effect of the timing of PMRT, both preceding and following 2-stage expander-implant breast reconstruction (IBR), and to statistically analyze the impact of timing on infection rates and the need for explantation. Methods: A comprehensive systematic review of the literature was conducted using the PubMed/Medline, Ovid, and Cochrane databases without timeframe limitations. Articles included in the analysis were those reporting outcomes data of PMRT in IBR published from 2009 to 2017. Chi-square statistical analysis was performed to compare infection and explantation rates between the two subgroups at p < 0.05. Results: A total of 11 studies met the inclusion criteria for this study. These studies reported outcomes data for 1565 total 2-stage expander-IBR procedures, where PMRT was used (1145 before, and 420 after, implant placement). There was a statistically significant higher likelihood of infection following pre-implant placement PMRT (21.03%, p = 0.000079), compared to PMRT after implant placement (9.69%). There was no difference in the rate of explantation between pre-implant placement PMRT (12.93%) and postimplant placement PMRT (11.43%). Conclusion: This study suggests that patients receiving PMRT before implant placement in 2-stage expander−implant based reconstruction may have a higher risk of developing an infection.